The David Versus the Bentall Procedure for Acute Type A Aortic Dissection - Biancari, Fausto; Mastroiacovo, Giorgio; Rinaldi, Mauro; Ferrante, Luisa; Mäkikallio, Timo; Juvonen, Tatu; Mariscalco, Giovanni; El-Dean, Zein; Pettinari, Matteo; Rodriguez Lega, Javier; Pinto, Angel G; Perrotti, Andrea; et al. (Journal of cardiovascular development and disease, 2024)
Background: Type A aortic dissection (TAAD) is a life-threatening condition which requires prompt diagnosis and surgical treatment. When TAAD involves the aortic root, aortic valve-sparing or Bentall procedures are the main surgical treatment options. Method: The subjects of this analysis were 3735 patients included in the European Registry of Type A Aortic Dissection (ERTAAD). Propensity score matching was performed by estimating a propensity score from being treated with the Bentall or the David procedure using multilevel mixed-effects logistics, considering the cluster effect of the participating hospitals. Results: A Bentall procedure was performed in 862 patients, while a David operation was performed in 139 patients. The proportion of aortic root replacement, as well as the different techniques of aortic root replacement, varied significantly between the participating hospitals (p < 0.001). After propensity score matching, we obtained two groups of 115 patients each, and no statistical differences were reported in terms of postoperative outcomes, except for the rate of dialysis, which was higher in the patients requiring a Bentall procedure (17.4% vs. 7.0%, p-value 0.016). In the unmatched cohorts, the David procedure was associated with a lower 10-year mortality rate compared to the Bentall procedure (30.1% vs. 45.6%, p-value 0.004), but no difference was observed after matching (30.0% vs. 43.9%, p-value 0.082). After 10 years, no differences were observed in terms of proximal aortic reoperation (3.9% vs. 4.1%, p-value 0.954), even after propensity score matching (2.8% vs. 1.8%, p-value 0.994). Conclusions: The David and Bentall procedures are durable treatment methods for TAAD. When feasible, it is advisable that the David procedure is performed for acute TAAD by surgeons with experience with this demanding surgical technique.
Keywords: type A aortic dissection; Bentall procedure; aortic root; David procedure